2019
DOI: 10.3892/etm.2019.7678
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics and probiotics in atopic dermatitis (Review)

Abstract: Recent years have brought additional data on the benefits of prebiotics and probiotics treatment in patients with atopic dermatitis. This review includes all the articles published in PubMed, Scopus, Embase and Cochrane databases until 05.06.2018. The terms used for the search were 'prebiotic', 'probiotic', 'atopic dermatitis', 'Severity Scoring of Atopic Dermatitis', and 'SCORAD'. There was an increase of the intestinal permeability reported in patients with atopic dermatitis and a reduction of the cutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 62 publications
(59 reference statements)
0
46
0
5
Order By: Relevance
“…In the context of allergic diseases, several studies based on murine and in vitro models have highlighted the potential role of Bifidobacterium in reducing inflammation through the production of anti-inflammatory cytokines and suppressing Th2 immune response and IgE production [92][93][94]. Moreover, Bifidobacterium produces short-chain fatty acids (SCFA) that decrease intestinal permeability and maintain the integrity of the intestinal barrier [95] to prevent the triggering of the immune response against antigens in the bloodstream [96]. In patients with atopic dermatitis (AD), the proportion of Clostridia, Clostridium difficile, Escherichia coli, and Staphylococcus aureus in the gut microbiome is higher than in healthy controls, and a reduction in short-chain fatty acid (SCFA)-producing bacteria (Bifidobacterium, Blautia, Coprococcus, Eubacterium, and Propionibacterium) is also observed [97,98].…”
Section: Early Aberrant Microbiota and Its Effect On Pediatric Diseasesmentioning
confidence: 99%
“…In the context of allergic diseases, several studies based on murine and in vitro models have highlighted the potential role of Bifidobacterium in reducing inflammation through the production of anti-inflammatory cytokines and suppressing Th2 immune response and IgE production [92][93][94]. Moreover, Bifidobacterium produces short-chain fatty acids (SCFA) that decrease intestinal permeability and maintain the integrity of the intestinal barrier [95] to prevent the triggering of the immune response against antigens in the bloodstream [96]. In patients with atopic dermatitis (AD), the proportion of Clostridia, Clostridium difficile, Escherichia coli, and Staphylococcus aureus in the gut microbiome is higher than in healthy controls, and a reduction in short-chain fatty acid (SCFA)-producing bacteria (Bifidobacterium, Blautia, Coprococcus, Eubacterium, and Propionibacterium) is also observed [97,98].…”
Section: Early Aberrant Microbiota and Its Effect On Pediatric Diseasesmentioning
confidence: 99%
“…In most previous studies, live forms of Lactobacillus and Bifidobacterium are the most investigated organisms, 5‐9,18‐25 while there have been limited studies of heat‐killed probiotics in adults 23,30 . Distinctively in the present study, we used RHT3201, which was tyndallized killed Lactobacillus rhamnosus (strain obtained from a Korean breastmilk‐fed infant) for investigating the therapeutic effect on AD in children.…”
Section: Discussionmentioning
confidence: 99%
“…However, long‐term use of these medications may induce several adverse effects 1‐3 . Previous meta‐analyses have suggested that exposure to environmental microbes or harmonized intestinal microbes can modulate the development of allergic diseases including AD 4,5 . Recently, microbes such as probiotic bacteria have been highlighted and considered candidates for immunomodulating pharmabiotics to prevent and treat allergic diseases; they have been mainly studied in AD 5‐9 …”
Section: Introductionmentioning
confidence: 99%
“…Notably, manufacturers frequently refer to these products as “drugs,” because these products are following the drug regulatory approval pathway. There are many examples of scientific literature suggesting that the further investigation of live microbial treatments may be fruitful for a range of disease states, such as anxiety and depression, Alzheimer's disease, allergies, acne, atopic dermatitis, cancer, diabetes, hypercholesterolemia, hyperammonemia, HIV, irritable bowel syndrome and inflammatory bowel disease, nonalcoholic steatohepatitis/nonalcoholic fatty liver disease, osteoporosis, phenylalanine hydroxylase deficiency, and vaccine delivery . For example, “psychobiotics” are a subset of live microbe therapies currently being explored that can confer a beneficial psychological effect in mental health disorders .…”
Section: Fda Considerationsmentioning
confidence: 99%